AIMS65 Scoring System for Predicting Clinical Outcomes Among Emergency Department Patients with Upper Gastrointestinal Bleeding - Nabiel, Rifaldy; Munawir, Al; Firdaus, Jauhar (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Several scoring systems were developed for early risk stratification in Upper Gastrointestinal Bleeding (UGIB) patients. AIMS65 score is a scoring system that only consists of five parameters, it might be used in daily clinical practice because of rapid and easy to calculate within 12 hours of admission. Objective: To evaluate the AIMS65 scoring system as a predictor of mortality, rebleeding events, need for endoscopic therapy, blood transfusion, and ICU admission for all causes of UGIB. Methods: We conducted a systematic review on PubMed, ScienceDirect, ProQuest, and Cochrane Library databases from the 2012 to 2022 publication period. We included either prospective or retrospective cohort studies that reported UGIB with all kinds of aetiologies who presented in the emergency department (ED), reported discriminative performance for each outcome, and reported the optimal cut-off of AIMS65. The primary measurement of discriminative performance for clinical outcomes includes mortality, rebleeding incidents, need for endoscopic therapy, blood transfusion, and ICU admission. Results: We identified 351 published studies, of which 20 were included in this study. Most of the studies reported discriminative performance for predicting mortality, which amounts to about 18 out of 20 studies. Rebleeding prediction was reported in 11 studies, need for endoscopic therapy in 5 studies, blood transfusion in 7 studies, and ICU admission in 2 studies. Most of the studies reported fair to excellent discriminative performance for predicting mortality, but in contrast for predicting rebleeding, the need for endoscopic therapy, blood transfusion, and ICU admission. Cut-off valuesâ‰¥ 2 are frequently reported to distinguish between high-risk and low-risk patients in mortality. Conclusion: AIMS65 can be applied to patients with UGIB in ED for predicting mortality, but not applicable for predicting rebleeding events, the need for endoscopic therapy, blood transfusion, and ICU admission. It enhances early decision-making and triage for UGIB patients.